The etiology of the Indian materialist Carvaka in the Mahabharata - Sevilla Rodríguez, Martín (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
The author analyzes passages of the great epic poem of India in which Hinduism carries out an etiologic interpretation of the legendary figure that represents the most distant heterodoxy.
Keywords: Indian philosophy; history of materialism; Ca¯ rva¯ ka; Maha¯ bha¯ rata